A prospective study of chest injuries and associated complications with special reference to surgical emphysema - Dangi, Sunil Kumar; Meena, Naresh; Parmar, Ashok (International Surgery Journal, 2018)
Background: Chest trauma (or thoracic trauma) is a serious injury of the chest. Thoracic injuries may present extremely dramatic clinical problem that demand rapid diagnosis, decision making and aggressive management. Thoracic injuries can range from simple single rib fracture to major thoracic vessel injury and pulmonary contusion. Objective of this study was to describe the clinical characteristics and risk factors of thoracic trauma patients, and to evaluate their relationship in the development of complications with special emphasis to surgical emphysema. Methods: Descriptive, prospective and analytical study of a cohort of patients with thoracic trauma who were followed up for a period of 30 days. Excluded from the study were those patients with moderate to severe cranio-encephalic trauma, long bone fractures, abdominal trauma, and patients who required mechanical ventilation. Results: A total of 102 patients met the inclusion criteria out of which 90(88.23%)patients were male and 12(11.77%) female with male to female ratio of 7.5:1. Patients having surgical emphysema were all male 21(21.56%). Most common mode of the injury seen was road traffic accidents in 80 (80.95%) patients, followed by assault in 9(9.52%) patients, bull horn injury and fall from height in 4(4.76%) patients. Other chest injury which was most commonly associated with surgical emphysema was haemothorax in 11(52.38%) patients, followed by pneumothorax in 7(33.33%) patients, pulmonary contusion in 6(28.57%) patients and flail chest in 3(14.26%) patients. The risk of complications increases significantly in patients with more than 2 rib fractures, in older patients and in the presence of some comorbidities such as COPD and pathologies that require anticoagulation. The risk of re-admittance is greater in patients older than 60 years. Conclusions: Patients with thoracic trauma who present with co-morbidities, are older than 60 years and have more than 2 ribs fractures may present with more complications. These factors should be contemplated in the evaluation, management and follow-up of these subjects.